KONSUMEN FARMASI DAN HARGA OBAT DI INDONESIA - Kusumastuti, Dora - (Widya Wacana: Jurnal Ilmiah, 2012)
Abstrack: A In the selection of cultural practice medicine by a doctor to the patient, who is also known aspharmacy consumers, there is a relationship a simetric information where the information is only held by one party, namely the grant of a fee of dokter. Dengan Large Pharmacyto the doctor, resulting in its higher drug prices would do not want to be paid by the consumer. Of structural factors of health, including, Doctor, Pharmacy Man power, and Large Pharmaceutical Company, and also of the laws that regulate each of these structural element shave not been reflected in a regulation that provides protection to the patients in the economy. And the absence of a rule governing the distribution of pharmaceutical processes, resulting in the consumer marketin this case is apatient, who becomes the victim, and only certain parties are benefited.Key word : Konsumen Farmasi, Pembangunan Hukum Farmasi, Mahalnya Harga Obat